2011
DOI: 10.1007/s11904-011-0091-7
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive Impact of Antiretroviral Treatment: Thinking Long-Term

Abstract: Combination antiretroviral therapy has significantly reduced morbidity and mortality with HIV infection. However, HIV-associated neurocognitive disorders persist at a relatively high prevalence rate despite successful systemic treatment. This paper reviews the current issues related to the neurocognitive impact of antiretroviral treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…The brain, in particular, represents a sanctuary for HIV-1 latency, where the provirus can persist due to the variable and poor penetration of antiretroviral drugs. 22,23 While viral replication was considered necessary for inflammation and neurodegeneration, recent studies showed a high prevalence of HAND even in long-standing aviremic patients. 24 We provide here a novel explanation for brain damage in the absence of viral replication, mediated by deregulation of BCLL1B that contributes to sustain HIV-1 latency and might also alter the expression of inflammationrelated genes.…”
Section: Resultsmentioning
confidence: 99%
“…The brain, in particular, represents a sanctuary for HIV-1 latency, where the provirus can persist due to the variable and poor penetration of antiretroviral drugs. 22,23 While viral replication was considered necessary for inflammation and neurodegeneration, recent studies showed a high prevalence of HAND even in long-standing aviremic patients. 24 We provide here a novel explanation for brain damage in the absence of viral replication, mediated by deregulation of BCLL1B that contributes to sustain HIV-1 latency and might also alter the expression of inflammationrelated genes.…”
Section: Resultsmentioning
confidence: 99%
“…NCI in the setting of cART is associated with synaptodendritic degeneration [7, 11, 12]. While the brain represents a sanctuary where HIV can persist due to suboptimal penetration of antiretroviral drugs [13], various studies highlighted the occurrence of NCI even in the setting of viral suppression [14, 15]. Chronic neuroinflammation is believed to drive neurodegeneration in cART-era HAND [7, 9, 16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…However, whether direct or indirect the link between inflammation in the CNS and manifestations of cognitive impairment is yet to be determined. The increase in the incidence of milder forms of HAND may be exacerbated due to the effects of aging in the infected population, although this remains controversial (McPhail and Robertson 2011). Additionally, it has been proposed that the brain may act as a tissue sanctuary for HIV due to limited drug penetrance into the CNS allowing for low levels of replication (McPhail and Robertson 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The increase in the incidence of milder forms of HAND may be exacerbated due to the effects of aging in the infected population, although this remains controversial (McPhail and Robertson 2011). Additionally, it has been proposed that the brain may act as a tissue sanctuary for HIV due to limited drug penetrance into the CNS allowing for low levels of replication (McPhail and Robertson 2011). However, the CNS penetrance of many antiretroviral drugs has since been evaluated, and drugs with improved CNS penetration yield better neurocognitive outcomes, suggesting this problem could be overcome with the proper ART regimen (Letendre et al 2004; Patel et al 2009; Smurzynski et al 2011).…”
Section: Introductionmentioning
confidence: 99%